ANALISIS KESENJANGAN DAERAH DAN KONVERGENSI PDRB PERKAPITA KABUPATEN/KOTA JAWA TIMUR SEBELUM DAN SETELAH DESENTRALISASI - ELWANA, YOZA AMMITA; SUTIKNO, -; KURNIASARI, WIDITA (MediaTrend, 2013)
The purposes of this study are; to analyzeÂ  regional disparities and the convergence before and after decentralization, determine the amount of speed of convergence that happen, and to discover the description of per capita income growth changing through Klassen typology. This research is conducted by using quantitative data with: Indeks Williamson Analysis; a simple OLS regression analysis (Ordinary Least Square); and Topologi Klassen Analysis. Conclusions of this study are; (1) there are a convergence occure within speed convergence is 0,34 before the decentralization and convergence with a speed of convergence as 0,42 happened after the decentralization, (2) by dividing into 4 quadrant in klassen typology measurement, the majority is in 4th quadrant where the District and City are remain left behind, and the movement of quadrant into 2nd quadrant is happened after the decentralization that means they belong to fast-growing region.